Influence of the loading speed on the results of examinations of road fitment on compression - D. N. Andrianov; S. V. Korneev (Литьë и металлургия)
In the article there is examined the influence of loading speed, and also of the dynamic parameters of the hydraulic testing presser and inflexibility of the test sample on the results of statistic examinations of road fitment on compression.